Pemanfaatan Media Pembelajaran Augmented Reality Untuk Meningkatkan Minat Belajar Siswa - Putri Indah Lestari; Eka Rosdianwinata; Deni Pratidiana (Universitas Mathla'ul Anwar Banten, 2026)
This research aims to determine the use of mathematics learning media through an Augmented Reality (AR) approach in increasing students' interest in learning at SMP 1 Menes on the topic of flat-sided solid shapes. Augmented Reality media was chosen as an innovative approach due to its ability to present interactive and engaging three-dimensional (3D) visualizations, making it easier for students to understand abstract concepts. The research method used was quantitative with a quasi-experimental design. The population in this study were grade VIII junior high school students who were divided into two groups: an experimental group that used Augmented Reality (AR) learning media and a control group that used a conventional method. Data were collected through learning interest questionnaires, observation, interviews, and documentation. The results of the study showed that the use of AR learning media can significantly increase students' interest in learning, with an average increase in the N-Gain Score of 72% compared to the control group which had a very low increase of 13%. This identifies that Augmented Reality media can be an effective solution for increasing students' interest in learning.